Neurolaw: A Concept in Development and Enforcement of Criminal Law in Indonesia - Fernando, Zico Junius; Agusalim, Agusalim; Utami, Ria Anggraeni; Albariansyah, Hamonangan; Sacipto, Rian (Jambura Law Review, 2025)
Neurolaw is an interdisciplinary field that combines law and neuroscience to enhance the understanding of human behavior, decision-making, and their legal implications. This approach is gaining global attention and has potential for application in Indonesia's criminal law system. Neurolaw sheds light on how factors related to the brain and nervous system like impulsivity, mental health issues, and environmental influences can affect criminal behavior and personal accountability. This research, using normative legal method, finds that neurolaw could be valuable in Indonesia's justice system for evaluating testimony, truth, and fairness. Techniques like brain scans and neuropsychological tests offer scientific support for statements made by defendants and witnesses, helping to ensure legal decisions are more objective and just. While neurolaw offers potential advancements for criminal law, it faces challenges in Indonesia. Neuroscience is a complex field that requires specialized knowledge, yet Indonesia currently has few experts in this area. Additionally, the required infrastructure such as brain scanning technology, advanced laboratories, and research funding is limited.